PENGARUH DIVERSIFIKASI TERHADAP RISIKO PORTOFOLIO SAHAM (KASUS 5 SAHAM SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA) - JUNAEDI, JUNAEDI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
The purpose of this study is to explain the effect of diversification on the risk of stock portfolio of mining sector in Indonesia Stock Exchange. Sampling techniques using is purposive sampling with 5 sample of stocks from the mining sector in the BEI. Analyzer uses variance-covariance. The results of this study are: 1) The risk on portfolio 1 share (ADRO) reached 7.2%. When MEDC shares were added, portfolio risk decreased significantly to 0.72%. BUMI shares were included, portfolio risk rose to 0.75%. When ANTM and PTBA stocks added portfolio risk increased respectively to 0.96% and 5.7%. 2) Diversification affects portfolio risk when the portfolio only forms up to 3 stocks are ADRO, MEDC and BUMI, so the initial hypothesis is accepted. However, when ANTM and PTBA stocks are added to the portfolio, the risk is increased so that the initial hypothesis is rejected for the 5 stock portfolio. Proportion of funds in portfolio 3 shares, namely; 81.3% (ADRO), 10.7% (MEDC) and 8% (BUMI) will generate portfolio risk of 0.75% and expected return of 2.5%.